Dancing Under the House: Woman & Absence in Israel - Baum, Rob (Richtmann Publishing, 2011)
This feminist participatory ethnography reflexively examines constraints on women in Palestinian culture in Northern Israel,as typified by differences in space, volume, musical rhythm, costume, convenience and honour. Observations were conducted at a haflah, orwedding party, held over several days, and subsequently through follow-up. The article does not essentialise Palestinian culture orundermine Arab women: the ethnographerâ€™s inclusion into the family paradoxically permitted her an â€œinsideâ€ perspective where bothPalestinians and Israelis could (or would) not go. In Israelâ€™s margins within margins, the lives of Arab Muslim women lie farthest fromthe nucleus of power. Literally dancing under the house also symbolically elided the bodies of women with the house, its foundations, subterrain,and hidden spaces, locating the domestic beneath or beyond the view of men. A small plastic doll performed as a simulacrum oftraditional Palestinian femaleness and domesticity in which women are best kept unseen. The article incorporates traditional storytelling,Prophetic hadith, and contemporary Palestinian poetry.